Condition of the hemostatic system in pregnant women with the threat of premature birth when using metabolic therapy - E. A. Panchuk (Kazimierz Wielki University, 2019)
130 pregnant women were examined with the threat of premature birth in the gestational age of 28-34 weeks: I group - 67 pregnant women with threatened preterm labor who received standard complex therapy in combination with metabolic therapy in the form of 300 mg of omega-3 polyunsaturated fatty acidsper day, group II - 63 pregnant women with threatened preterm labor who received only standard complextherapy. Analyzing the state of the hemostasis system, the following changes were revealed: an increase in the level of fibrinogen and prothrombin time, indicating a hypercoagulative process.Were observed a decrease in fibrinogen level, an increase in platelet count and activated partial thromboplastin time and a decrease in prothrombin time after treatment with the use of metabolic therapy, indicating the antithrombotic and antiaggregatory effects of metabolic therapy.